Musical education in the primary schools of Hungary, Romania, Serbia and Slovakia - Váradi, Judit (Array, 2019)
The study is a part of international research, the aim of which was to examine a less known aspect of music education in four Central European countries: Hungary, Romania, Serbia and Slovakia. The research focused on school students aged between 8 and 12, N=805. The study explored the educational structure and curricula of the participating countries. It also put the emphasis on the teaching methods for introducing music to student; furthermore, it examined the presentation of live music. In the course of our research we examined the role of social variants with regard to the cultural activities of the children. Moreover, we explored the correlation between parental cultural capital and children’s interest in classical music. Another important aspect of our study was the international comparison focusing on the differences and similarities in music education between various countries. The third issue examined in detail was the relationship between the formal and non-formal education, i.e. how the extra-curricular education (such as experience pedagogy and concert pedagogy) can become part of the everyday pedagogical work of the schools.